2013
DOI: 10.1016/j.neuint.2013.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in brain support cells: Implications for stroke severity

Abstract: Stroke is one of the leading causes of adult disability and the fourth leading cause of mortality in the US. Stroke disproportionately occurs among the elderly, where the disease is more likely to be fatal or lead to long-term supportive care. Animal models, where the ischemic insult can be controlled more precisely, also confirm that aged animals sustain more severe strokes as compared to young animals. Furthermore, the neuroprotection usually seen in younger females when compared to young males is not observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 258 publications
(275 reference statements)
2
49
0
1
Order By: Relevance
“…First, aged animals after stroke sustain more severe brain injuries compared to young animals [26][27][28], and it's highly probable that different brain damage will induce different angiogenesis. Second, intravascular flow rate is an important mediator for angiogenesis, and previous studies showed that aging is greatly related to blood flow velocity and flow volume [29].…”
Section: Discussionmentioning
confidence: 99%
“…First, aged animals after stroke sustain more severe brain injuries compared to young animals [26][27][28], and it's highly probable that different brain damage will induce different angiogenesis. Second, intravascular flow rate is an important mediator for angiogenesis, and previous studies showed that aging is greatly related to blood flow velocity and flow volume [29].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies suggest that these effects do not persist in older female rodents (Leon et al, 2012; Sohrabji et al, 2013b; Strom et al, 2011). In addition to the loss of the anti-inflammatory properties of 17βE2 in young, Ovx mice, recent studies strongly suggest that the anti-inflammatory effects of 17βE2 are lost during a period of prolonged hypoestrogenicity in middle-aged (Suzuki et al, 2007a), or reproductively senescent (Selvamani and Sohrabji, 2010a; Sohrabji et al, 2013a), mice. 17βE2 also suppresses a systemic post-stroke immunosuppression phenotype in animal models that closely mimics a peripheral immunosuppressive phenotype seen in human patients (Ritzel et al, 2013; Zhang et al, 2010).…”
Section: Mechanisms Of Estrogen Neuroprotectionmentioning
confidence: 99%
“…Several excellent reviews address cell type-specific anti-inflammatory mechanisms of 17βE2 in microglia (Habib and Beyer, 2015; Vegeto et al, 2008), astrocytes (Acaz-Fonseca et al, 2014), endothelial cells (Sohrabji et al, 2013a), and oligodendrocytes (Arevalo et al, 2010) during neurological injury. In young and middle-aged preclinical animal models of stroke, 17βE2 inhibits the activation of the pro-inflammatory transcription factor, nuclear factor-κβ, which induces transcription of numerous cytokines such as tumor necrosis factor-α (TNFα), chemokine ligand 2 (CCL2), interleukin-6 (Vegeto et al, 2008).…”
Section: Mechanisms Of Estrogen Neuroprotectionmentioning
confidence: 99%
See 1 more Smart Citation
“…This allows astrocytes to play a critical and leading role in the detoxification of the CNS microenvironment and, due to their involvement in the fine-tuning of brain inflammatory responses, in the local inflammatory regulation under acute devastating conditions [7,11,12] . Astroglia cells convey a multitude of cellular actions which all can be attributed a protective role such as growth factor supply, reduction of excitotoxicity, minimizing oxidative stress, influencing the interplay of immunological cells and innate immune responses, and regulating water balance as well as astrocyte swelling [11,[13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%